The heterosis, heterobeltiosis, and the yielding ability of hybrids of three parental crossings of soybean (Glycine max) - DIANA SOFIA HANAFIAH; LUTHFI AZIZ MAHMUD SIREGAR; KHAIRUNNISA LUBIS; HARYATI HARYATI; FADILLAH RAHMADANA (Society for Indonesian Biodiversity, 2023)
Abstract. Hanafiah DS, Siregar LAM, Lubis K, Haryati, Rahmadana HF. 2023. The heterosis, heterobeltiosis, and the yielding ability of hybrids of three parental crossings of soybean (Glycine max) Merill]. Biodiversitas 24: 1032-1038. One of the ways to increase productivity is by assembling new superior cultivars. The base population of a new superior cultivar is first provided as a population with morphological traits correlated with yield. One method for enhancing a plant's characteristics is to cross between parents with various characteristics. This study aimed to examine the value of heterosis and heterobeltiosis of generation F1.1 from a cross of three soybean parents between the Grobogan, Anjasmoro and Dega 1 varieties and predict soybean yields using multiple linear regression models. The soybean varieties Grobogan, Anjasmoro, and Dega 1 were employed as parents in this study. Each variety used as parental material has specific characters. Population diversity of F1.1 with superior traits from the combination of the parents' traits is anticipated to result from the crosses of three soybean varieties as parents. Multiple linear regression models were used in the prediction procedure to determine the soybean yield. The results showed that the value of heterosis and heterobeltiosis on the character of the number of pods per plant and the weight of 100 seeds per plant had positive values, respectively, 26.856%; 5.676%; 16.889% and 5.689%. The result of the best coefficient of determination was 0.6460 in the F1.1 genotype.